Inhibitory effect of dendroaspis natriuretic peptide on spontaneous contraction in gastric antral circular smooth muscles of guinea pigs - Guo Hui-shu; Cai Zheng-xu; Wu Tai-hua; Xu Jing; Qiu Yang; Xu Wen-xie (Acta Pharmacologica Sinica, 2016)
Aim: To determine whether the natriuretic peptide receptor (NPR) is present in the stomach of guinea pigs and to investigate the effect of dendroaspis natriuretic peptide (DNP) on the gastric motility of guinea pigs and its mechanism. Methods: The distribution of the NPR was analyzed by autoradioimmunography. The spontaneous contraction of gastric antral circular muscles of guinea pigs was recorded by a 4-channel physiograph. The whole cell patch-clamp technique was introduced to record calcium-activated potassium currents in the gastric myocytes isolated by collagenase. Results: The NPR existed in the gastric fundus, gastric body, and gastric antrum of guinea pigs, and its density was largest in the gastric antrum. DNP inhibited spontaneous contraction and exhibited a dose-dependent manner. The DNP-induced inhibition was diminished by LY83583 (a guanylate cyclase inhibitor) and was potentiated by zaprinast (a cGMP-sensitive phosphoesterase inhibitor). The inhibitory effect of DNP on spontaneous contraction was also inhibited by tetraethylammonium (a non-selective potassium channel blocker); 10 nmol/L DNP increased the calcium-activated potassium currents in the gastric circular myocytes of guinea pigs. Conclusion: The NPR is most common in the gastric antrum of guinea pigs. DNP significantly inhibits gastric motility in the gastric antrum of guinea pigs. The inhibitory effect occurs via a cGMP-dependent pathway, and a calcium-activated potassium channel may be also involved in the relaxation induced by DNP in gastric antral circular smooth muscles.